Metabolomics and proteomics analyses of zebrafish exposed to mesaconitine from Aconitum plants reveal marked reductions in lipid, glycolytic pathways - Eunyoung Park; Ji-ho Lee; Jae Won Oh; Hwa-Kyung Lee; Hye Suk Lee; Jeong-Han Kim; Jihyun Lee (Ecotoxicology and Environmental Safety)
Aconitum species have been widely used for thousands of years across Asia and North America, primarily in traditional Chinese medicine, where their rootstocks are commonly included in herbal formulations. Mesaconitine is a major benzoyl diterpenoid alkaloid in Aconitum roots, but its potential toxic effects on metabolism are unknown. This study investigated the effects of mesaconitine exposure in zebrafish through an integrative analysis of metabolomic and proteomic data. Three zebrafish groups (n = 6 each) were exposed to mesaconitine at 0 μg/L (Control), 8 μg/L (Low), or 80 μg/L (High) for 48 h. We observed significant alterations in both protein and metabolite levels following mesaconitine exposure. The results revealed 135 differentially expressed proteins, with 63 upregulated and 72 downregulated, alongside 57 differentially expressed metabolites. The analysis also revealed significant changes in key metabolic pathways, including glycerophospholipid metabolism, alanine, aspartate, glutamate metabolism, and arginine biosynthesis indicating disruptions in lipid and amino acid metabolism. Proteomic analysis showed disruptions in oxidative phosphorylation, the tricarboxylic acid (TCA) cycle, and respiratory electron transport, indicating a broad impact on energy metabolism. The combined metabolomic and proteomic data suggested coordinated changes in metabolic pathways and energy balance. Integrative metabolomic and proteomic changes induced by mesaconitine exposure, suggesting a coordinated reprogramming of metabolic pathways and energy homeostasis. This study provides a detailed molecular understanding of the complex metabolic and proteomic alterations in zebrafish following mesaconitine exposure and offers valuable insights into the mechanisms of toxicity induced by this compound.